Effect of montmorillonite clay on physical properties of HDPE/ HGS composites - Gümüş, Beril (Afyon Kocatepe Üniversitesi)
Recently, there has been an increasing interest in enhancing the physical properties of polymer nanocomposites. In the present study, the effect of montmorillonite (MMT) clay ratio (0, 1, 5, 10 and 15 wt.%) on the physical properties of the high-density polyethylene (HDPE)/ hollow glass spheres (HGS) composites were investigated. The hollow glass spheres ratio is 20% by weight. After the mixture obtained from the extruder was granulated, test specimens were produced using an injection molding machine. Physical tests were applied such as melt flow index (MFI), moisture content (MC), Vicat softening point (VSP), heat deflection temperature (HDT), Limit oxygen index (LOI). The nanoclay dispersion was examined by X-ray diffraction (XRD). Images of HDPE/HGS/MMT-clay composites were taken with Scanning electron microscopy (SEM). The results obtained show that heat deflection temperature, Vicat softening point, and melt flow index decreased gradually as the MMT-clay content increased. The LOI decreased with increase in the MMT-clay content from 0 to 15wt. %. MC increased with increase in the MMT-clay content from 0 to 1 wt. %. MC didn’t change with further increasing of MMT-nanoclay content to 10 percent by weight. Then, MC increased with increase in the MMT-clay content from 10 to 15 wt. %.

Son zamanlarda, polimer nanokompozitlerin fiziksel özelliklerinin geliştirilmesine yönelik artan bir ilgi vardır. Bu çalışmada, montmorillonit (MMT) kil oranının (ağırlıkça% 0, 1, 5, 10 ve 15) yüksek yoğunluklu polietilen (HDPE) / içi boş cam küreler (HGS) kompozitlerinin fiziksel özellikleri üzerindeki etkisi araştırıldı. İçi boş cam küre oranı ağırlıkça % 20'dir. Ekstrüderden elde edilen karışım granüle edildikten sonra, bir enjeksiyon kalıplama makinesi kullanılarak test numuneleri üretildi. Erime akış indeksi belirleme testi (MFI), nem miktarı belirleme testi (MC), Vicat yumuşama noktası belirleme testi (VSP), yük altında eğilme sıcaklığı belirleme testi (HDT), sınırlayıcı oksijen indeksi belirleme testi (LOI) gibi fiziksel testler uygulandı. Nanokil dispersiyonu, X-ışını kırınımı (XRD) ile incelendi. HDPE / HGS / MMT-kil kompozitlerinin görüntüleri Taramalı elektron mikroskobu (SEM) ile alınmıştır. Elde edilen sonuçlar, MMT-kil içeriği arttıkça ısıl çarpılma sıcaklığının, Vicat yumuşama noktasının ve erime akış indeksinin kademeli olarak azaldığını göstermektedir. LOI, MMT-kil içeriğinin ağırlıkça yüzde 0'dan 15'e yükselmesiyle azaldı. MC, MMT-kil içeriğinin ağırlıkça yüzde 0'dan 1'e artmasıyla artmıştır. MC, MMT-kil içeriğinin ağırlıkça yüzde 10'a yükseltilmesiyle değişmedi. Daha sonra, MC, MMT-kil içeriğinin ağırlıkça % 10'dan% 15'e yükselmesiyle arttı.
Montmorillonite kilinin HDPE/ HGS kompozitlerinin fiziksel özellikleri üzerindeki etkisi
Keywords: Nanoclay; Hollow Glass Spheres; High Density Polyethylene; Physical Properties; Nanokil; Cam Küreler; Yüksek Yoğunluklu Polietilen; Fiziksel Özellikler